2015
DOI: 10.1155/2015/315043
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Osteopontin Gene Polymorphism (rs1126616), Osteopontin Levels in Urine and Serum, and the Risk of Urolithiasis: A Meta-Analysis

Abstract: Objective. Previous studies have investigated the relationships between osteopontin gene polymorphism rs1126616 and OPN levels and urolithiasis, but the results were controversial. Our study aimed to clarify such relationships. Methods. A meta-analysis was performed by searching the databases Pubmed, Embase, and Web of Science for relevant studies. Crude odds ratios (ORs) or standardised mean differences with 95% confidence intervals (CIs) were calculated to evaluate the strength of association. Publication bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
2
5
0
1
Order By: Relevance
“…However, no study has previously shown the effect of the SNP on circulating levels of OPN in patients with different stages of CKD. Previous reports have shown no differences in OPN levels between different genotypes of the SNP [51,52,53]. Our results agree with the previous literature as the different genotypes do not modify the OPN levels, and more advanced stages of CKD show increased levels of OPN.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, no study has previously shown the effect of the SNP on circulating levels of OPN in patients with different stages of CKD. Previous reports have shown no differences in OPN levels between different genotypes of the SNP [51,52,53]. Our results agree with the previous literature as the different genotypes do not modify the OPN levels, and more advanced stages of CKD show increased levels of OPN.…”
Section: Discussionsupporting
confidence: 92%
“…Apart from CVE, the rs1126616 polymorphism has also been found to be associated with CKD [50], urolithiasis [51], and to the prevalence of lupus nephritis [52]. However, no study has previously shown the effect of the SNP on circulating levels of OPN in patients with different stages of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests it is part of the body’s defense mechanism in urine against pathological CaOx crystallization [48], which shows different functions of OPN from it in the renal tissue. As being shown in a meta-analysis, in addition to urine, significantly lower OPN levels were detected also in the serum of urolithiasis patients as compared with the normal controls [49]. The decrease in serum aspartic acid in the FFJQC groups may imply the expression of serum OPN.…”
Section: Discussionmentioning
confidence: 84%
“…Currently, there is only one meta-analysis available on the subject which revealed positive association of SPP1 coding region genetic variant (rs1126616:C > T) and lower serum and urine osteopontin levels with increased risk of developing urolithiasis [40], however, they did not include any other SPP1 polymorphism (including SPP1 promoter polymorphisms investigated in this study) in the analysis, which limits the usefulness and broader applicability of that study.…”
Section: Discussionmentioning
confidence: 98%